2020
DOI: 10.12785/ijcds/090609
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and Controlling High-Speed Vehicles Via CQI in LTE-A Systems

Abstract: One of the most serious problems facing the community around the world is car accidents. These accidents occur mainly due to the high-speed of vehicles. Thus, the paper aims to capture, track, and control high-speed vehicles using LTE-A mobile networks to avoid high-speed situations as well as decrease the number of accidents. The paper assumes that all vehicle drivers are now days carrying their mobiles that can be considered as mobile network user equipment (UE). This paper presents an innovative tracking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The result of each model concludes that both transmission methods are reliable for merging 5G cellular systems. In [13], the authors proposed an integrated system utilizes the 5G wireless cellular integrated with satellite communication systems by taming many downlink channels of the satellite link to manage the new 6G system. With the terrestrial's satellite, the satellite receivers will be directed to the LEO-system are communicated to the 5G systems or base stations.…”
Section: Related Workmentioning
confidence: 99%
“…The result of each model concludes that both transmission methods are reliable for merging 5G cellular systems. In [13], the authors proposed an integrated system utilizes the 5G wireless cellular integrated with satellite communication systems by taming many downlink channels of the satellite link to manage the new 6G system. With the terrestrial's satellite, the satellite receivers will be directed to the LEO-system are communicated to the 5G systems or base stations.…”
Section: Related Workmentioning
confidence: 99%
“…From the test results, it is found that in the room the best RSSI value is when the sending LoRa is placed on the 6th floor, this happens because the receiving LoRa placement is II. 4 Calculates the waiting time between sending LoRa and receiving LoRa. 5…”
Section: ) Indoor Testingmentioning
confidence: 99%
“…The Internet of Things (IoT) plays a very important role in various sectors such as education, agriculture, plantations, and smart cities [1], [2], [3], [4], [5]. In the plantation sector, IoT can be used to send the presence status of field workers working for a company.…”
Section: Introductionmentioning
confidence: 99%